Brincando de gênero: a identidade trans na infância e adolescência e o direito à retificação do prenome e do gênero no registro civil. - Soares, Camilla Danielle (2021)
The recognition of LGBTQIA+ rights by the Brazilian legal system has been hindered increasingly due to the omission of the Legislative Power and the existence of a strong conservative group within the National Congress. To make up for this unjustifiable legislative omission, the Judiciary is often called to action by the transgender population in order to determine the effectiveness of their rights. In this sense, the present research intends to analyze how Brazilian Federal Supreme Court is basing its rulings regarding transgender people‘s right to change their name and gender indication on the civil registry, specially those who are still children and adolescents. For that, concepts of sex, gender, sexual orientation and gender identity were approached, mainly through Judith Butlers‘ works. Then, some questions about the legal protection of transgender children and adolescents were examined. At the end, some norms about the right to a name were evaluated, as well as the possibilities and means of altering data from the civil registry, highlighting the judgment of the Direct Action of Unconstitutionality No. 4275 / DF by the Brazilian Federal Supreme Court. The methodology adopted for the elaboration of this study is characterized as qualitative and its execution consisted of the review of the votes of the ministers of the Brazilian Federal Supreme Court in the light of Consultative Opinion No. 24/2017 of the Inter-American Court of Human Rights and the theory of Judith Butler on the topic in question. In a subsidiary way, it followed the bibliographic and documental procedure, as well as the comparative method. Thus, with the development of this study, the expectation is to provide an open space of positive and reliable dialogues so that people can recognize trans identity in childhood and adolescence and that they can understand that transgender children and adolescents deserve specific and more assertive protection put in place to recognize their rights recognized, for they are subject to marginalization and social exclusion.